School Stress Coping Strategies Checklist - Katarina Mackova; Andrea Gavlakova (Communications - Scientific letters of the University of Zilina, 2010)
This paper deals with school stress and describes coping strategies used in load situations. Empirical research reveals what extent of stress pupils of elementary schools perceive as well as what coping strategies are most commonly utilised. Based on the findings we can conclude that the extent of the stress perceived by the sample group of school children is moderate and they resort to coping strategies such as ”avoidant action“ and ”distracting action“.